Targeting GIRK Channels for the Development of New Therapeutic Agents - Walsh, Kenneth (Frontiers in Pharmacology, 2011)
G protein-coupled inward rectifier K+ (GIRK) channels represent novel targets for the development of new therapeutic agents. GIRK channels are activated by a large number of G protein-coupled receptors (GPCRs) and regulate the electrical activity of neurons, cardiac myocytes and β-pancreatic cells. Abnormalities in GIRK channel function have been implicated in the patho-physiology of neuropathic pain, drug addiction, cardiac arrhythmias and other disorders. However, the pharmacology of these channels remains largely unexplored. In this paper we describe the development of a screening assay for identifying new modulators of neuronal and cardiac GIRK channels. Pituitary (AtT20) and cardiac (HL-1) cell lines expressing GIRK channels were cultured in 96-well plates, loaded with oxonol membrane potential-sensitive dyes and measured using a fluorescent imaging plate reader. Activation of the endogenous GPCRs in the cells caused a rapid, time-dependent decrease in the fluorescent signal; indicative of K+ efflux through the GIRK channels (GPCR stimulation versus control, Z’-factor = 0.5-0.7). As expected this signal was inhibited by addition of Ba2+ and the GIRK channel toxin tertiapin-Q. To test the utility of the assay for screening GIRK channel blockers, cells were incubated for 5 minutes with a compound library of Na+ and K+ channel modulators. Ion transporter inhibitors such as 5-(N,N-hexamethylene)-amiloride and SCH-28080 were identified as blockers of the GIRK channel at sub-micromolar concentrations. Thus, the screening assay will be useful for expanding the limited pharmacology of the GIRK channel and in developing new agents for the treatment of GIRK channelopathies.